The effect of restaurant service quality on customer satisfaction: a conceptual paper/ Fatin Nabila Mohd Nazri, Derweanna Bah Simpong and Naziatul Aziah Mohd Radzi - Mohd Nazri, Fatin Nabila; Simpong, Derweanna Bah; Mohd Radzi, Naziatul Aziah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The objective of this study is to propose a conceptual study of the effect of restaurant service quality on customer satisfaction in the casual restaurant segment. Using the DINESERV research model, this study improves the existing service quality literature by considering different variables from the elements of service quality such as physical environment and employee service quality, so as to understand the needs and wants of customers in a dining experience. With regard to the practical perspectives, this study will benefit not only those managing casual restaurants in Malaysia but also other restaurant segments. Close scrutiny of the service quality dimensions will benefit the management, especially the marketers of casual restaurants who want to retain and attract new customers.